The factors affecting older people’s participation in the labour market: Policy implications - Khairul Hanim Pazim; Noor Fzlinda Fabeil; Roslinah Mahmud; Juliana Langgat; Lim, Fui Yee Beatrice (Zes Rokman Resources, 2021)
The growing proportion of older people in many nations has sparked policymakers' interest in issues impacting older people's well-being, including concerns addressing support for older people, economic security, and familial living arrangements. This study looks at the relationship between intergenerational transfers, co-residence, and labour participation among 4,059 Malaysians aged 60 and above, using data from the Fifth Malaysian Population and Family Survey 2014 (MPFS-5). Determinants of older Malaysians participating in the labour market were identified using binary logistic regression after controlling for major demographic, health, socioeconomic and intergenerational support variables. The findings of this study have a number of key implications for future practices, with the goal of supporting the government in developing labour market regulations aimed at older people. This is to ensure older people's economic independence in old age, notwithstanding the fact that not all older people are able to participate in the labour market due to health issues. To guide present and future labour market strategies, a comprehensive, holistic, and interdisciplinary strategy embracing all aspects of ageing such as gender, health, education, and family is essential. Policies must also consider the nation's multi-ethnic society, including the needs of the elderly in all segments. It is timely to promote active and productive ageing while honouring family values in caring for the elderly as Malaysia prepares to become an ageing nation in the near future.